MicroRNA-875-5p inhibits the growth and metastasis of cervical cancer cells by promoting autophagy and apoptosis and inhibiting the epithelial-mesenchymal transition - Liang, Yingxiu; Li, Chunyang; Hou, Xiaohong; Lin, Yiguang; Cheng, Jing (Frontiers in Oncology, 2024)
Introduction MicroRNA-875-5p (miR-875-5p) is a cancer-related microRNA. It has been demonstrated that miR−875−5p participates in the development of various types of cancer such as hepatocellular carcinoma, gastric carcinoma, prostate and bladder cancer. Previous research suggested that miR-875 is implicated in the development of cervical cancer cells. However, the exact role and function of miR−875−5p in cervical cancer remain unexplored. It is important to examine the role and function of miR-875-5p and the associated signaling pathway, as the findings may have diagnostic and therapeutic significance. Thus, in this study, we investigated the effect of miR-875-5p on the growth and metastasis of cervical cancer cells and the possible underlying mechanisms. Methods Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression of miR-875-5p in cervical cancer cells and normal cervical epithelium. After overexpression or co-expression of miR-875-5p in cells, the changes in cell function were analyzed. Western blot was used to detect the expression changes of epithelial-mesenchymal transition (EMT) -related proteins and autophagy-related proteins. Results Functional studies demonstrated that miR-875-5p overexpression significantly inhibited the proliferation, migration, invasion, and EMT, and promotes apoptosis and autophagy of cervical cancer cells., while miR-875-5p knockdown promoted the proliferation, migration, invasion, and EMT, and inhibited apoptosis and autophagy cervical cancer cells. Furthermore, Western blot results showed that overexpression of miR-875-5p downregulated the expressions of N-cadherin, Snail, Vimentin and microtubule-associated protein 1 light chain 3B I (LC3B I). Conversely, miR-875-5p upregulated the expression of E-cadherin. Conclusion In conclusion, our findings suggest that miR-875-5p functions as a tumor inhibitor suppressing the growth and metastasis of cervical cancer. Overexpression of miR-875-5p inhibits malignant behavior and promotes autophagy and apoptosis in cervical cancer cells. These findings advance our understanding of the role and function of miR-875-5p in cervical cancer and could facilitate the development of early genetic markers or biomarkers and therapeutic targets for cervical cancer.